Targeting the dopamine D1 receptor or its downstream signalling by inhibiting phosphodiesterase‐1 improves cognitive performance. (3rd June 2018) - Pekcec, Anton; Schülert, Niklas; Stierstorfer, Birgit; Deiana, Serena; Dorner‐Ciossek, Cornelia; Rosenbrock, Holger
Abstract : Background and Purpose: Insufficient prefrontal dopamine 1 (D1 ) receptor signalling has been linked to cognitive dysfunction in several psychiatric conditions. Because the PDE1 isoform B (PDE1B) is postulated to regulate D1 receptor‐dependent signal transduction, in this study we aimed to elucidate the role of PDE1 in cognitive processes reliant on D1 receptor function. Experimental Approach: Cognitive performance of the D1 receptor agonist, SKF38393, was studied in the T‐maze continuous alternation task and 5‐choice serial reaction time task. D1 receptor/PDE1B double‐immunohistochemistry was performed using human and rat prefrontal brain sections. The pharmacological activity of the PDE1 inhibitor, ITI‐214, was assessed by measuring the increase in cAMP/cGMP in prefrontal brain tissue and its effect on working memory performance. Mechanistic studies on the modulation of prefrontal neuronal transmission by SKF38393 and ITI‐214 were performed using extracellular recordings in brain slices. Key Results: SKF38393 improved working memory and attentional performance in rodents. D1 receptor/PDE1B co‐expression was verified in both human and rat prefrontal brain sections. The pharmacological activity of ITI‐214 on its target, PDE1, was demonstrated by its ability to increase prefrontal cAMP/cGMP. In addition, ITI‐214 improved working memory performance. Both SKF38393 and ITI‐214 facilitated neuronal transmission in prefrontal brain slices. Conclusion and Implications: We hypothesize that PDE1 inhibition improves working memory performance by increasing prefrontal synaptic transmission and/or postsynaptic D1 receptor signalling, by modulating prefrontal downstream second messenger levels. These data, therefore, support the use of PDE1 inhibitors as a potential approach for the treatment of cognitive dysfunction.